Peran Greenpeace Dalam Mengurangi Penggunaan Minyak Sawit Kotor Pada Perusahaan Unilever Indonesia Tahun 2015 - 2019 - Risa Arsiyat, (2020)
Forests are important for the survival of creatures on earth, Indonesia's forests are the 3rd largest forests in the world after Brazil and Congo. Every year Indonesia's forests continue to experience deforestation, thus threatening the survival of flora, fauna and indigenous peoples who depend on the forest for their livelihoods. Deforestation that occurs due to changes in the function of forests into plantations one of which is oil palm. Indonesian palm oil exports which continue to increase every year because of demand, this makes the entrepreneurs continue to open up land for plantations. One large company that relies on Indonesian palm oil is Unilever. Seeing this, Greenpeace as an international organization that has a role to protect the environment acts to protect Indonesia's forests from deforestation due to oil palm. This research will discuss the role of Greenpeace in the use of crude palm oil at Unilever. The author uses international organizational theory, with derivatives of the concept of campaign, negotiation and sustainable development with data collection techniques study literature, observation. The results of this study are that Greenpeace has carried out its role as an NGO through campaigns and negotiations and assisted in sustainable development and in 2019 Unilever successfully used sustainable palm oil as much as 95% of its total use